A silver ion potentiometric sensor based on a synthesized 1,3-benzocrown macrocyclic diamide as neutral carrier - Capangpangan, Rey Y. (Philippine Journal of Science, 2012)
A synthesized benzo-crown macrocycle, 1,15-diaza-3,4;12,13-dibenzo-5,8,11-trioxacyclooctadecane-2,14-dione (1,3-MDA), was employed as an ionophore in the fabrication of polymeric ion-selective electrodes (ISE) for silver ion. The electrode membrane ingredients consisting of PVC/Plasticizer (o-NPOE) ratio of 0.94 and ionophore/additive ratio of 2.0 exhibited near Nernstian response of 57.75 mV/decade activity of Ag+ over a linear concentration range of 10-6 M to 10-3 M (R2 = 0.9921). The dynamic response time of this electrode was ~2 min at pH range of 3-9. The sensor has a limit of detection (LOD) of 6.32 x 10-7 M, and was stable for at least one month. Initial investigation on the applicability of this new ISE for the detection of silver ions in photographic wastewater sample and comparison of its performance with conventional method (Atomic Absorption Spectroscopy) were also reported.